2016
DOI: 10.1142/s0219622014500199
|View full text |Cite
|
Sign up to set email alerts
|

Performance Management of Taiwan’s National Hospitals

Abstract: This study aimed to conduct operation performance evaluations of Taiwan’s national hospitals during the period 2005–2008 and also propose appropriate suggestions for operation performance improvements. 28 national hospitals were selected as study objects and six input variables and three output variables were filtered as evaluation measures. Data envelopment analysis model was used for annual operation performance evaluation, and Malmquist productivity index for intertemporal operation performance change analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…This could be an explanation of why Availability of specialists -SC19 (34.5%) was ranked second in Human resources criterion. These findings are consistent with , Yeh and Cheng (2016) and Ketabi et al (2018) whose DEA models qualified "number of staff" as a critical input in EDs. Regarding Supplies, medicines and accessories cluster (Figure 7b), Availability of accessories and instrumentation -SC23 was ranked in the first place.…”
Section: Phase 2: Final Criteria and Sub-criteria Weightssupporting
confidence: 87%
See 3 more Smart Citations
“…This could be an explanation of why Availability of specialists -SC19 (34.5%) was ranked second in Human resources criterion. These findings are consistent with , Yeh and Cheng (2016) and Ketabi et al (2018) whose DEA models qualified "number of staff" as a critical input in EDs. Regarding Supplies, medicines and accessories cluster (Figure 7b), Availability of accessories and instrumentation -SC23 was ranked in the first place.…”
Section: Phase 2: Final Criteria and Sub-criteria Weightssupporting
confidence: 87%
“…Such outcomes are an evidence of the regular and poor performance of these EDs in the wild. A similar finding was presented by Yeh and Cheng (2016) who detected that 60% of national Taiwanese hospitals ran an inefficient performance. It is then important to further seek the reasons explaining the aforementioned results.…”
Section: Phase 2: Final Criteria and Sub-criteria Weightssupporting
confidence: 82%
See 2 more Smart Citations
“…Chen's study [ 34 ] showed that public hospitals outperformed non-public ones during the research period even though private hospitals had become larger and more group-oriented. However, Chen [ 35 ] and Yen [ 36 ] found that private hospitals have better technological efficiency than the public hospital. To make a more sophisticated analysis, we classified the ownership into the public, university-affiliated, foundation, and religious hospitals instead of only dividing it into public and private hospitals to reflect real managerial ownership in Taiwan.…”
Section: Discussionmentioning
confidence: 99%